PERFORMANCE OF KERALA TOURISM INDUSTRY - N.S. Krishnan Namboothiri and Ashish Varughese (JIMS, 2010)
Tourism as a phenomenon means the movement of people both within and across the national borders. It is an era of tourism, an era which includes the growth of leisure travel around the world is expected to grow in drastic proportions. In this travel era almost all countries in the world is either reaping benefits from tourism or planning to harvest benefits from tourism in the years to come. Kerala better known as “God’s Own Country” is one of the most sought after tourist destinations in Asia. Kerala is the first state in India to announce industrial status for tourism as early in 1986 and announced various incentives and subsidies to attract investors. It is necessary that the tourist destination can provide right type of facilities at the right time at the right quality. This paper tries to analyses the performance of tourism industry of the state